BUDAYA PENGASUHAN ANAK DALAM KELUARGA DI KELURAHAN KAMPUNG DAGANG KECAMATAN RENGAT - Ningsih, Hilda Septia Ningsih Septia; Baheram, Murni Baheram; Natuna, Daeng Ayub Natuna Ayub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract:The problem in this study is: Does the culture in a family child care by parents has been quite good. This study aimed to: determinethe culture of parenting at home in the village of Kampung Trade District of Rengat, and benefit from this research: (1) Provide conceptual contribution in the development of the concept o ffamily education,(2) to increase the knowledge of parents in the care of children in the family. This type of research is deskrpitif with quantitative approaches, this method aim stoprovidea systematic overview of the state of the object of ongoing research on the care of children in the family culture. Where research is Kampung Village Trade District of Rengat. The populationin this study is the parents who have children that no trade sub- district Kampung Village Trade District of Rengat, which amounted to 120 people, while a sample of 54 parents. The results showed that: Culture in Family childcare in the village of Kampung Trade Rengat districts classified as moderate. Of thefourdominant indicator is Permissive Parenting Culture with 3.12 Mean and standard deviation of 0.74 with a high interpretation. Authoritative parenting culture with mean 2.73 and standard deviation was 0.73 with interpretation. Parenting culture ignores 2.46 with a standard deviation of 0.73 with the interpretation being. Authoritarian Parenting and Culture with Mean 2.31​​with a standard deviation of 0.73 with the interpretation being. Based on the defined criteria, it can be concluded that the culture of permissive parenting on children in the family in the village of Kampung Trade District of Rengat be the cause of the child do deeds that are less good. Keywords: Culture, Parenting, Child, Family